FAKTOR – FAKTOR YANG MEMPENGARUHI FISCAL STRESS PADA PEMERINTAH KABUPATEN/KOTA DI PROVINSI SUMATERA SELATAN - Citra, Anastasia Julia; Masnila, Nelly; Mubarok, Muhammad Husni (Universitas Muhammadiyah Palembang, 2024)
This research aims to determine the factors that can impact fiscal stress in Regency/City Governments in South Sumatra Province from 2018 to 2022. The resaerch uses a sample of Regency/City Governments in South Sumatra Province with moderate regional financial capacities. Secondary data sourced from publications released by the Supreme Audit Agency is utilized. The research employs multiple linear regression to test the hypotheses, specifically using the R² test, partial test, and simultaneous test, analyzed with SPSS (Statistical Package for the Social Sciences) Version 26.The result is that regional original income and capital expenditures have a positive and statistically significant impact on fiscal stress. balancing funds and decentralization fiscal have a negative and significant impact on fiscal stress.